The Study of Sociological Factors Affecting Social Health among Students of Shahid Chamran University of Ahwaz - karim rezadoost; alihossein hosseinzadeh; ayoub rostami (توسعه اجتماعی)
The purpose of this study was to investigate the sociological factors affecting social health among students of Shahid Chamran University of Ahvaz. The research method is correlational and analytical. The statistical population includes all the students of Shahid Chamran University of Ahvaz in the second semester of the year 2017-2018. The sample title is intended. The findings of this study show that students' social health is moderately upward and there is a direct relationship between variables of access to facilities and services, quality of life, communication skills, religiosity and gender with social health variable and the relationship between age and social health. There is a reverse, but there is no significant relationship between socioeconomic status variables in both mental and objective dimensions with social health. The results showed that there is a significant difference between gender and social health. The results of multivariate regression show that the research variables account for 13.1% of the changes in social health.